Application of cellulase enzyme obtained from fermentation of sewage sludge on rice straw into sugar - Alam, Md. Zahangir; Mukhtaruddin, Muna Tasnim; Hamzah, Mohd. Salleh (2010)
One of the major applications of cellulase lies in the process of hydrolysis of cellulosic or lignocellulosic material to produce sugar which can be further fermented to produce ethanol. This study focuses on the application of cellulases produced from fermentation broth of sewage sludge on lignocellulosic materials such as rice straw and waste paper. In addition, the enzyme also has been applied on sewage sludge. The amount of sugar produced from the selected biomasses indicated whether the enzyme produced is in fact suitable to be used on large scale for the production of bioethanol. For the application on waste paper and rice straw, process parameters such as particles sizes and enzyme dosage were optimized in order to achieve high yield of sugar produced. While for the sewage sludge, the enzyme dosage and sludge concentration (percentage of Total Suspended Solid, TSS) were varied to observe the amount of reducing sugar. Using the cellulase enzyme with the activity of 45 U/ml, the waste paper showed the strongest susceptibility towards enzymatic hydrolysis reacted with cellulase enzyme. The amount of reducing sugar from the optimized condition for both waste paper and rice straw were 34.4 mg/ml and 18 mg/ml respectively which gave 68 and 36% of percentage of saccharification respectively. Whereas, for the application on the sewage sludge, after varying the sludge concentration and enzyme dosage, no reducing sugar was obtained after the saccharification process.